AFOXOLANER EFFICACY AGAINST GENERAL DEMODECOSIS IN DOGS BASED ON SKIN HISTOPATHOLOGY - Christian, Jeremy; Jayanti, Putu Devi; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2023)
Demodicosis is the most common skin disease found in dogs, caused by the proliferation of Demodex sp. mites. Based on the distribution of the lesions, demodicosis is divided into local and generalized. This study aims to determine the efficacy of Afoxolaner against General Demodicosis in dogs. A 1.5 year old mixed-breed male dog weighing 7.8 kg came to the Internal Laboratory, Faculty of Veterinary Medicine, Udayana University, with anorexia, weakness, and hair loss in the facial area, around the ears, neck, limbs, sides, back and extremities. On physical examination found alopecia, erythema all over the body, crusts, pustules in the medial caudal limb. Dogs exhibit high levels of pruritus. Routine haematological examination showed that the dog had anemia and leucocytosis. Diagnosis based on microscopic examination of deep skin scraping is Demodicosis. The prognosis in this case is fausta. Case dogs were treated with Afoxolaner (NexGard®), Azithromycin Dihydrate (10mg/kgBB, PO, q24h) and Chlorpheniramine maleate (4mg/day, PO, q12h) for a week. Histopathological examination of the skin before drug administration revealed pieces of demodex in the hair follicles, furunculosis, inflammatory cell infiltration of the stratum spinosum and dermis layer, necrosis accompanied by haemorrhagic exudate, follicular dilatation, and peri folliculitis. Post-therapy, the results of histopathological examination showed good results, with no pieces of mites found, the size of the follicle returned to normal, and no inflammatory cell infiltration was seen in the peri follicle. On the 10th day it was seen that the dog's condition had improved, the results of the skin scraping showed a reduced number of mites in one field of view. Afoxolaner should be given once a month for three months to eliminate and prevent mite infection in dogs.